2021
DOI: 10.1155/2021/9981915
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Potency of Medicinal Plants including Artemisia annua and Oxalis corniculata against Multi-Drug Resistance E. coil

Abstract: Antibacterial activity of ethanolic and aqueous extracts of two medicinal plants including Oxalis corniculata (EtOc, AqOc) and Artemisia annua (EtAa, AqAa) as well as A. annua essential oil (EoAa) was investigated on multi-drug resistance (MDR) E. coli. Microdilution and agar well diffusion methods were used to determine the minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC) as well as the inhibition zone. The phytconstituents of these products were analyzed using Reverse-phase Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…These pronounced synergistic effects were observed in the combinations of artemisinin with metronidazole [30], petroleum and methanol ether extracts of A. annua with chloramphenicol [31], chrysosplentin, penduletin and chrysoeriol with norfloxacin, chrysoeriol with ciprofloxacin [39], extract of A. khorassanica with amikacin and imipenem [41] and the combination of DhL with chloramphenicol [38], for instance. Importantly, these results provide promising future options for the treatment of infectious diseases caused by MDR pathogens, whereby MDR strains of E. coli [32], A. baumanii [41], P. aeruginosa and K. pneumoniae [36,38] and S. aureus [30,39,40] have become sensitive towards antibiotics when combined with the products derived from the Artemisia plants. In addition, some of the Artemisia compounds were equally potent as common antibiotics, as seen with artemisinin and artemisinic acid which are derived from A. annua, and were shown to exert antibiotic effects that were similar to those observed for clarithromycin against S. aureus and S. epidermidis [30], for instance.…”
Section: Discussion Summarymentioning
confidence: 99%
See 3 more Smart Citations
“…These pronounced synergistic effects were observed in the combinations of artemisinin with metronidazole [30], petroleum and methanol ether extracts of A. annua with chloramphenicol [31], chrysosplentin, penduletin and chrysoeriol with norfloxacin, chrysoeriol with ciprofloxacin [39], extract of A. khorassanica with amikacin and imipenem [41] and the combination of DhL with chloramphenicol [38], for instance. Importantly, these results provide promising future options for the treatment of infectious diseases caused by MDR pathogens, whereby MDR strains of E. coli [32], A. baumanii [41], P. aeruginosa and K. pneumoniae [36,38] and S. aureus [30,39,40] have become sensitive towards antibiotics when combined with the products derived from the Artemisia plants. In addition, some of the Artemisia compounds were equally potent as common antibiotics, as seen with artemisinin and artemisinic acid which are derived from A. annua, and were shown to exert antibiotic effects that were similar to those observed for clarithromycin against S. aureus and S. epidermidis [30], for instance.…”
Section: Discussion Summarymentioning
confidence: 99%
“…Some studies showed that the plant product exhibits a very low or even no antimicrobial activity when applied alone [28,29,31,32,39]. However, the products were synergistically active upon combination with established synthetic antibiotic drugs, even enhancing the efficacy of the tested antibiotics in some instances.…”
Section: Discussion Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…Empirically in Kalimantan, people use the leaves as a medicine for stomach aches, canker sores, and coughs 16 . Several previous reports found that the ethanolic extract of the O. corniculata herb could inhibit Escherichia coli and S. aureus 19,20 . However, no studies have reported the profound antibiofilm activity of this plant.…”
Section: Introductionmentioning
confidence: 94%